CREATION CUSTOMER VALUE UNTUK MENINGKATKAN PURCHASE INTENTION PADA JASA SABILA TRANSPORT - Ria Purnamasari (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
To improve the services of the Transport Sabila. 3) Influence Perceived emotional value onSabila Transport services. 4) Effect of Perceived social value Purchase intention to improvethe services Sabila Transport. Respondents this study of 120 consumers by the results ofquestionnaires. Distributing questionnaires done manually or directly to Transport Sabilaservices ever used the services to be Sabila Transport and leasing transactions in SabilaTransport Services. Research and testing of the instrument using validity and reliability test.While the classic assumption test using test heteroscedasticity, multicollinearity, andnormality. Based on This study aims to determine how much influence Creation to improvecustomer value Purchase intention at Sabila Transport services consisting of : 1) Effect ofPerceived price value Purchase intention to improve the services of the Transport Sabila. 2)Influence Functional quality value Purchase intention the result that out of the four variables.Ie consisting of : 1) variable Perceived price value, 2) variable quality Functional value, 3)variable Perceived emotional value and 4) variable Perceived social value very positiveinfluence on Purchase intention. By showing the value of the coefficient amounted to68.4%.